2018
DOI: 10.1111/iej.12894
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for the silent information regulator 2 homologue 1 (SIRT1) in periapical periodontitis

Abstract: These findings suggest that SIRT1 may stimulate angiogenesis in periapical granulomas by triggering the proliferation of endothelial cells and inducing VEGF and VE-cadherin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several studies have explored the associations between SIRT1 and VEGF in angiogenesis. An in vitro study of Kudo et al (2018) showed that mRNA expression of SIRT1 in Human umbilical vein endothelial cells (HUVECs) peaked after 6 h of incubation with a SIRT1 activator, resveratrol. However, VEGF mRNA showed delayed expression, 4 h later than SIRT1, suggesting that SIRT1-mediated stimulation of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the associations between SIRT1 and VEGF in angiogenesis. An in vitro study of Kudo et al (2018) showed that mRNA expression of SIRT1 in Human umbilical vein endothelial cells (HUVECs) peaked after 6 h of incubation with a SIRT1 activator, resveratrol. However, VEGF mRNA showed delayed expression, 4 h later than SIRT1, suggesting that SIRT1-mediated stimulation of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that sirtuins are involved in the pathogenesis of apical periodontitis (Table 1). Kudo et al evaluated the importance of SIRT1 in apical granulomas and they found that SIRT1 expression was rather high in gingival lesions compared with healthy gingival tissues (Kudo et al, 2018a;Kudo et al, 2018b). Furthermore, SIRT1 was shown to be colocalized with Ki-67, vascular endothelial growth factor (VEGF), VEcadherin, and 8-hydroxy-2′-deoxyguanosine (8-OHdG) in…”
Section: Apical Periodontitismentioning
confidence: 99%
“…Endodontic research community has been mostly concerned with microbiology, histopathology, diagnosis and treatment of AP (de Miranda & Colombo, ; Kruse, Spin‐Neto, Reibel, Wenzel, & Kirkevang, ; Kudo et al, ; Li, Tong, & Ling, ; Ricucci, Loghin, Gonçalves, Rôças, & Siqueira, ). Yet, understanding the aetiology of disease requires other information than that related to biological mechanism in the individual.…”
Section: Introductionmentioning
confidence: 99%